Pengenalan Konsep Perpustakaan dalam Lirik Lagu "Perpustakaan Jalanan" Karya Senartogok - Selviana Selvi; Atiqa Nur Latifa Hanum; Amriani Amir (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2023)
In the lyrics to the song "Library of the Streets", Senartogok uses a standard choice of words, which may sound foreign to ordinary people. Like the words sigil, the mask-cutter, the exclamation mark of anxiety, the face of knowledge, the spirit of the tv, and the heart component wire. Words like that will certainly be difficult to understand for ordinary people who rarely hear these words. The purpose of this study was to find out the concept and meaning of the library contained in the lyrics of the song "Library of the Streets" by Senartogok. The research method uses a qualitative approach, as well as data collection through observation and overall observation of the research object, namely the lyrics of the song "Library of the Streets". Descriptive data analysis with Roland Barthes's semiotic theory analysis. The results of the study show that the lyrics of the song Senartogok provides a form of attitude and criticism regarding how the culture of reading nowadays has begun to be pushed aside by instant information media, such as TV and social media, where the street library points directly at reading sources in open spaces. Media, where books can be presented without any restrictions, is a true remedy for human alienation due to technological developments. The street library that was established has provided a unique warmth, such as the combination of urban flow with the excitement of the desire to open space.